Estimation of the local sublimation front velocities from neutron radiography and tomography of particulate matter. (16th January 2020) - Gruber, S.; Vorhauer, N.; Schulz, M.; Hilmer, M.; Peters, J.; Tsotsas, E.; Foerst, P.
Highlights: A new method is proposed to visualize local sublimation front velocities. Neutron radiography and tomography is a valuable tool to investigate freeze-drying. Radial drying fronts of each particle were observed. A planar drying front evolving from the bottom of the bed could be observed. Abstract: With this study it was possible for the first time to visualize local sublimation front velocities of particle beds with neutron radiography and tomography. Few theoretical studies exist on the freeze-drying behavior of particle beds, but no experimental validation of the models exists basically due to the limits of traditional measurement techniques. The study was conducted at the neutron imaging facility ANTARES at the Heinz Maier Leibnitz Centre. Maltodextrin particles (x = 3550 µm) with different solid concentrations (c = 0.05 w/w; c = 0.2 w/w) were investigated. For the radiography measurements, it is shown that a main sublimation front evolves from the bottom to the top of the bed. Tomography measurements (for particles with c = 0.05 w/w) confirmed the formation of radial drying fronts throughout the bed in addition to the main sublimation front. In general, both methods show overall good agreement and will be a valuable tool for further investigations.